ECOOP 2012 -- Object-Oriented Programming 26th European Conference, Beijing, China, June 11-16, 2012, Proceedings - Noble, James (Programming and Software Engineering, 2012)
This book constitutes the refereed proceedings of the 26th European Conference on Object-Oriented Programming, ECOOP 2012, held in Beijing, China, in June 2012. The 27 revised full papers presented together with two keynote lectures were carefully reviewed and selected from a total of 140 submissions. The papers are organized in topical sections on extensibility, language evaluation, ownership and initialisation, language features, special-purpose analyses, javascript, hardcore theory, modularity, updates and interference, general-purpose analyses.